Expression and correlation of SOCS3 and Eotaxin mRNA and proteins levels in nasal mucosal tissue of allergic rhinitis patients - Kang, Zhaopeng; Xu, Lian; Ai, Ping; Qu, Wei; Li, Tang; Wang, Lixin (Frontiers in Immunology, 2025)
ObjectiveThis study aims to investigate the expression and interaction mechanisms of Suppressor of Cytokine Signaling 3 (SOCS3) and Eotaxin in the nasal mucosal tissues of patients with Allergic Rhinitis (AR).MethodsIn this retrospective study, we selected nasal mucosa tissues from 35 AR patients as the AR group, and nasal mucosa tissues from 22 patients with isolated nasal septum deviation as the control group. Utilizing reverse transcription polymerase chain reaction (RT-PCR) techniques, we measured the expression levels of SOCS3 mRNA and Eotaxin mRNA in both groups. Additionally, immunohistochemical methods were employed to assess the protein expression of SOCS3 and Eotaxin in these tissues.ResultsThe average optical density value of SOCS3 protein in the AR group was 0.270 ± 0.05, significantly higher than 0.160 ± 0.04 in the control group (P<0.01); the average optical density value of Eotaxin protein in the AR group was 0.240 ± 0.04, also significantly higher than 0.164 ± 0.03 in the control group (P<0.01). At the mRNA level, the ratio of SOCS3 mRNA to GAPDH in the AR group was 0.83 ± 0.27, and the ratio of Eotaxin mRNA to GAPDH was 0.71 ± 0.21, both significantly higher than 0.32 ± 0.11 and 0.22 ± 0.08 in the control group. Besides, the expression levels of SOCS3 protein and mRNA in the nasal mucosal tissues of AR patients were positively correlated with the expression of Eotaxin protein and mRNA (r=0.927, P<0.01; r=0.854, P<0.01).ConclusionThe high expression of SOCS3 and Eotaxin in the nasal mucosal tissues of AR, as well as the positive correlation between them, suggest that they may play an important role in the pathogenesis of AR. This study provides new experimental evidence for in-depth understanding of the pathogenesis of AR and new potential targets for the treatment of AR.